An exploratory study of the reasons why adult students attend, persist, and complete graduate Homeland Security programs - Cupp, Orville Shawn (Kansas State University, 2009)
Since the events of 9/11, homeland security has emerged as an important and growing field of study. It is based upon information which is drawn from a diverse network of multiple disciplines that serve a variety of professions. Due to the embryonic nature of this field and the complicated nature of the mix of professions served, college and university administrators and faculty need to develop a better data-based sense about why students enroll, attend, and complete homeland security-related educational programs. As one might expect with a new field like homeland security studies, little research concerning student enrollment, persistence, and attendance patterns has been conducted to date. This study used the Dillman Tailored Design Mode of Internet Survey methodology to collect data (Dillman 2007; Dillman, Smith, & Christian, 2009). Data were collected from students attending homeland security-related graduate programs during the 2009 fall semester. Data concerning program delivery modes (online, face-to-face, and hybrid) and generational demographics (Baby Boomers, Generation X, Generation Y), were used as the basis to examine the elements of student enrollment, persistence, and completion patterns in this study. In order to accomplish data reduction and decrease error, an Exploratory Factor Analysis (EFA) was conducted to sort loaded factors from the 30 item survey instrument. Eight factors were obtained all with over |.7| load values including four having positive values and four having negative values. These eight factors were used as dependent variables to conduct a MANOVA with generational demographic and program delivery mode as independent variables in order to determine if any significance existed. Significance was discovered between one of the four factors and the two independent variables with low to medium effect size based upon partial eta squared. The intersection of the two dependent variables of generational demographic and program delivery mode was not found to be significant. Further MANOVA with the four negative load factors of EFA were found to be significant in regards to program delivery mode and the intersection of program delivery mode and generational demographic. The significance found was with low to medium effect size based upon partial eta squared.
Keywords: Adult education; Higher education; Education, Higher (0745)